Femmes et violence de masse. - Myre, Nadia; Uzel, Jean-Philippe (Hors-série, 2018)
"Si tous les groupes humains sont touchés par la violence à grande échelle, les femmes la subissent sous des formes spécifiques, comme en témoignent les assassinats systémiques des femmes et des filles autochtones en Amérique du Nord et en Amérique latine, ou encore les nombreux conflits armés (Syrie, Lybie, Birmanie, entre autres) dans lesquels le viol est érigé en arme de guerre. Les deux phénomènes peuvent d'ailleurs se recouper puisque l'un des tout premiers féminicides à avoir été qualifié et documenté comme tel en Amérique est celui ayant été perpétré contre les femmes mayas durant la guerre civile guatémaltèque au début des années 1980. Cependant, les femmes ne sont pas seulement les victimes de la violence de masse, puisqu'elles sont aussi les premières à témoigner et dénoncer pour faire barrage à cette violence. Ce numéro hors-série regroupe des articles et des projets visuels qui décrivent et analysent la violence de masse liée au genre. Il s'agit de réfléchir sur la manière de représenter cette violence et d'en témoigner, d'autant plus qu'elle est bien souvent rendue invisible et inaudible par le patriarcat, le colonialisme, les intérêts politiques en présence ou l'impéritie de l'État."
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Épistémologies du Sud : lectures critiques du féminisme décolonial - Femenías, María Luisa (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2019)
Publié en 2000, le livre de Boaventura de Sousa Santos — un sociologue émérite portugais — intitulé Critique de la raison indolente a eu un grand impact au Brésil comme dans le reste de l’Amérique Latine (De Sousa Santos, 2000/2003). Il y développait ce qu’il a appelé « les Épistémologies du Sud » global en opposition aux « Épistémologies du Nord », global également. De Sousa Santos entendait par « Épistémologies du Sud » les connaissances, théories et savoirs qui réfléchissent avec créativit...
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 5-Autrice; _Nettoyé

Equivocation, Translation, and Performative Interseccionality: Notes on Decolonial Feminist Practices and Ethics in Latin America - de Lima Costa, Claudia (ANGLO SAXONICA, 2013)
In this paper I offer a brief overview of the academic debates about post-colonial theories and the concept of coloniality, seeking to map out their Latin American translations, especially from the perspective of feminist theories in relation to the coloniality of gender. By emphasizing an intersectional approach to understand the gendered character of coloniality, decolonial feminists are seeking innovative ways of articulating new epistemologies or “saberes propios”. However, in these debates little attention has been given to the issue of the travels and translations of decolonial feminisms in Latin America. In focusing on the vexed issue of translation, I want to explore some of the challenges Latin American decolonial feminists are facing today.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Representaciones del espacio, el tiempo y las mujeres indígenas en fotografías, siglos XIX-XXI - Yujnovsky, Ines (Memoria y Sociedad, 2017)
Este trabajo se propone comprender la incidencia de las relaciones de poder que ciertas representaciones temporales acerca de grupos indígenas pueden ejercer en nuestra comprensión pasada y actual. Diversas imágenes reprodujeron ideas de indígenas que, aunque estuvieran vivos, mostraban una cultura asimilada a un pasado de amplias dimensiones. Por lo tanto, para comprender el proceso de invisibilización de la diversidad indígena en la cultura nacional, es relevante considerar los mecanismos de montaje discursivo —visuales y textuales—, vinculados con las nociones temporales de indios viviendo en un supuesto tiempo remoto. Atendiendo a ello, se analizan los procesos de montaje, desde la producción de las fotografías hasta la edición y presentación de imágenes, tanto en la prensa como en postales, publicaciones científicas y de divulgación, para ver cómo a veces pequeños cambios de encuadre, contraste, retoque o selección pueden incidir en la construcción de diversas historias, en la comprensión y en los sentidos construidos y en pugna.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

On Video Games: the Visual Politics of Race, Gender and Space - Murray, Soraya (International library of visual culture ; 27, 2018)
Today over half of all American households own a dedicated game console and gaming industry profits trump those of the film industry worldwide. In this book, Soraya Murray moves past the technical discussions of games and offers a fresh and incisive look at their cultural dimensions. She critically explores blockbusters likeThe Last of Us, Metal Gear Solid, Spec Ops: The Line, Tomb Raider and Assassin's Creed to show how they are deeply entangled with American ideological positions and contemporary political, cultural and economic conflicts.As quintessential forms of visual material in the twenty-first century, mainstream games both mirror and spur larger societal fears, hopes and dreams, and even address complex struggles for recognition. This book examines both their elaborately constructed characters and densely layered worlds, whose social and environmental landscapes reflect ideas about gender, race, globalisation and urban life. In this emerging field of study, Murray provides novel theoretical approaches to discussing games and playable media as culture. Demonstrating that games are at the frontline of power relations, she reimagines how we see them - and more importantly how we understand them.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Critical media studies, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Género y postcolonialismo en la creación videográfica: mujeres que escriben con la cámara y seducen en la pantalla - López, Xesqui Castañer (Dossiers feministes, 2014)
Postcolonialismo y feminismo utilizan conceptos comunes para el análisis y de/construcción de las narrativas dominantes. En países donde la colonización ha hecho estragos, las mujeres ponen en valor su empoderamiento como protagonistas de su destino. En esta línea las mujeres han aportado sus propuestas feministas para una nueva visión de lo colonial/postcolonial. Este trabajo pretende hacer un chequeo por aquellos trabajos videográficos de mujeres que, después de haber sido colonizadas, han realizado una descolonización cultural, situando su creatividad en varios continentes.
Keywords: 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créatrice; _À vérifier-Cinéma

Feminist Geographies in Latin America: Epistemological Challenges and the Decoloniality of Knowledge - Silva, Joseli Maria; Ornat, Marcio Jose (Journal of Latin American Geography, 2020)
This paper analyzes the growth of gender studies in Latin America, despite facing resistance in the scientific field and from the advance of conservative policies on the continent. It also addresses the challenges that feminist research faces in colonized spaces. To develop our argument, we draw on the scholarship of feminist researchers in Brazil, Mexico, and Argentina, such as Veleda da Silva and Lan (2007), Silva and Vieira (2014), Silva, César and Pinto (2015), Colombara (2016), Lan (2016), Veleda da Silva (2016), Ibarra-García and Escamilla-Herrera (2016), Zaragocin-Carvajal, Moreano-Venegas, and Álvarez-Velasco (2018), and Silva and Ornat (2019). This paper also examines the difficulties that Latin American feminist geographies face in establishing their own foundations in a globalized world where the geopolitics of global knowledge of geography is increasingly structured by the epistemological centralization of the Anglophone northern hemisphere.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Corporeal Identities, Maternal Artivism: A New Decolonial Approach to the Study of Latin American Women Artists - Demori, Lara (Arts, 2019)
Stemming from Grosfoguel’s decolonial discourse, and particularly his enquiry on how to steer away from the alternative between Eurocentric universalism and third world fundamentalism in the production of knowledge, this article aims to respond to this query in relation to the field of the art produced by Latin American women artists in the past four decades. It does so by investigating the decolonial approach advanced by third world feminism (particularly scholar Chandra Talpade Mohanty) and by rescuing it from—what I reckon to be—a methodological impasse. It proposes to resolve such an issue by reclaiming transnational feminism as a way out from what I see as a fundamentalist and essentialist tactic. Following from a theoretically and methodological introduction, this essay analyzes the practice of Cuban-born artist Marta María Pérez Bravo, specifically looking at the photographic series Para Concebir (1985–1986); it proposes a decolonial reading of her work, which merges third world feminism’s nation-based approach with a transnational outlook, hence giving justice to the migration of goods, ideas, and people that Ella Shohat sees as deeply characterizing the contemporary cultural background. Finally, this article claims that Pérez Bravo’s oeuvre offers the visual articulation of a decolonial strategy, concurrently combining global with local concerns.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé